Morphological, ecological and molecular characterization of Pyropia vietnamensis (Bangiales, Rhodophyta) from the Konkan region, India - Kavale, Monica Gajanan; Kazi, Mudassar Anisoddin; Sreenadhan, Nived; Singh, Veerendra Veer (Phytotaxa, 2015)
Pyropia vietnamensis is one of the most luxuriously growing seaweed in Konkan coast, India. In the present study we attempted to explore the morphology, ecology and molecular characteristics exhibited by P. vietnamensis and its taxonomic implications. We described the effects of ecological parameters on the variability of morphological characters. The water motion was found to be one of the most important ecological parameter that governs the plant morphology. The plant was found to grow on entire intertidal region and this may be one of the possible reasons for high morphological variation among the taxa in this region. The molecular analysis utilizing cox 1 gene sequences clearly revealed the close relation of Indian and Brazilian specimens with only 0-1 bp intraspecific variation. The present study provides a beginning to a clearly required detailed study of the morphology, ecology and genetic diversity showed by Pyropia species from Indian waters.